Elucidating the bonds between organizational ethical climate and corporate environmental citizenship - Tay, Lee Chin; Tan, Fee Yean; Khulida Kirana Yahya, (Penerbit Universiti Kebangsaan Malaysia, 2018)
The aim of this paper is to examine the relationship between organizational ethical climate and corporate environmental citizenship. Drawing upon Resource-Based View (RBV) theory, this study develops a research framework to explain the relationship between organizational ethical climate and corporate environmental citizenship. A quantitative approach was employed to test the relationship between organizational ethical climate and corporate environmental citizenship. Grade 7 construction companies were selected as the target respondents. Systematic sampling technique was used to ensure that every member of the sampled population has equal chances of being selected as a respondent. However, self-administered questionnaires were used to collect data. The findings showed that organizational ethical climate is significantly related to corporate environmental citizenship. It also showed that if the construction companies wish to optimize corporate environmental citizenship, they need to prioritize organizational ethical climate. In addition, discussion, implications, directions for future research, and conclusion of the study were also highlighted.